Falls in the elderly: Prevention and care in COVID-19 situations - Thaniwattananon, Ploenpit; Kumkong, Malee (Journal of Medicine and Health Sciences, 2023)
Thailand has now become a completely aged society. The elderly are considered vulnerable and requires the preparation of a health care system to support. The deceleration in aging, both physical and psychological changes, as well as chronic diseases causing the elderly to have a high risk of falling. Falls in the older population and their consequences are one of the leading causes of disability. They significantly reduce quality of life and lead to loss of independence and impaired social functioning. The ongoing Coronavirus disease (COVID-19) pandemic, social distancing and the lockdown policy increase the barriers of the elderly to maintain their usual health. During the COVID-19 outbreak, falls and slips were the most common mechanism of injury, therefore more attention on fall prevention and care protocols for effective care of the elderly are needed: (1) a comprehensive geriatric heath assessment and fall risk screening: personal illness, activity of daily living, and nutrition; (2) internal and external environmental assessment, and (3) fall prevention guidelines focusing on strengthening physical health and improving the environment for safety both in houses and in the community and create innovation to prevent falls and reduce injuries. Preventing home hazards that cause fall injuries to elderly population should become a priority in geriatric care so that the elderly can have a better health and promote good quality of life.